PERANCANGAN SISTEM INFORMASI KOPERASI SMK NEGERI 1 KOTA PARIAMAN - Firdaus Firdaus (Horizon, 2021)
Cooperative in SMK 1 Pariaman City is cooperative that is on developing and have a routine enough high, but the process processing the data still using a manual system. In overcoming these problems an information system is needed in order to simplify the performance of cooperative devices, then the authors designed a cooperative information system at SMK Country 1 city Pariaman. There are several methods in this writing such as research methods to develop an system the interactive model used has several stages in forming an information system, namely system planning, system analysis, system design and application of system. The result of this writing is a cooperative information system design that uses the testing phase with the blackbox method, namely system testing that focuses on functional spesifications and software and the tester can define a collection of input conditions in testing the functional specifications of the program.